Defining Aesthetic in the Use in Metaverse - Feng, Menghan; Liu, Zhen (CV TOPAZART, 2023)
This study examines the aesthetic of art in many generations and technology. This study is motivated by the recent surge in the artist, creators, and modeler activity on the part of creators, investors, and traders. We begin by proposing a novel classification of the existing literature that ranges from the old era through the metaverse. It focuses on art’s aesthetics concerning painting, visual design, and modeling. The research method uses a qualitative approach with document data. The research findings show that the current stage of cultural importance, or the social conditions, or what art is, or does art instead represent art itself? On the other hand, a design for a system is playing at a modeling desk, trying out alternative solutions for the geometric, topological, behavioral, and functional specifications of a planned factory with small concrete model parts. And the last digital makeup, both creatively and psychologically. The face is so important to humans because it’s the first thing we see in another person.